An Unfortunate Comparison of Apples to Oranges: Comment on Jensma (2016). Issue 3 (September 2017) - Rosik, Christopher H.
In reporting the findings of her outcome study of Along-side's intensive outpatient psychotherapy (IOP) program for Christian missionaries and clergy, Jensma (2016) offered an unfortunate "apples-to-oranges" comparison to my outcome data on Link Care's IOP, which resulted in a largely erroneous discussion section. In this comment, I briefly describe the nature of the problematic comparison and provide some additional analyses of my earlier outcome research to highlight my concerns. I close with the assertion that extant data can only support the conclusion that Alongside and Link Care IOP programs both appear to be beneficial to participants and equivalently so at three month follow up.